Prospects for avoiding crises with liberalized capital flows - Williamson, John (Estudios de Economía, 2016)
The history of Latin America’s relations with the international capital market has not been a happy one. Debt crises have recurred with monotonous regularity ever since the 1820’s, about three years after the first loans were contracted by newly independent countries. Despite the theoretical benefits that we all know capital flows can bring, it is easy to believe that Latin America’s history would have been happier had the region never borrowed a penny. The liberalization of capital flows will make the region more rather than less exposed t such crises. Are there nevertheless any reason for believing that the future may be happier than the past? I shall argue that there are in fact three such reasons: the changing composition of capital inflows, the possibility that countries will learn by experience, and the analogous possibility that capital markets will also learn by experience and come to take a longer term view.